27th International Conference on Optical Fiber Sensors 2022
DOI: 10.1364/ofs.2022.th3.3
|View full text |Cite
|
Sign up to set email alerts
|

Towards large-scale entanglement-enhanced interferometry

Abstract: We report progress measuring Earth’s rotation with entangled photons. In our 2 km fiber Sagnac interferometer, we achieve milliradian sensitivity with cw light, find a preliminary signal, and work towards injecting 2-photon NOON states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…16 A Sagnac phase shift on a two-photon NOON state was observed in, 17 and the current sensitivities allow the measurement of the Earth's daily rotation. 18 Here we review how mechanical rotations affect photon bunching in a Hong-Ou-Mandel (HOM) setup. It was shown that the temporal distinguishability of photons is affected by low-frequency mechanical rotations resulting in a shift of the HOM dip.…”
Section: Introductionmentioning
confidence: 99%
“…16 A Sagnac phase shift on a two-photon NOON state was observed in, 17 and the current sensitivities allow the measurement of the Earth's daily rotation. 18 Here we review how mechanical rotations affect photon bunching in a Hong-Ou-Mandel (HOM) setup. It was shown that the temporal distinguishability of photons is affected by low-frequency mechanical rotations resulting in a shift of the HOM dip.…”
Section: Introductionmentioning
confidence: 99%